TINJAUAN TATA RUANG ERGONOMI PELAYANAN RAWAT JALAN BERDASARKAN KONSEP ERGONOMI GUNA MENUNJANG EFEKTIVITAS KERJA DI PUSKESMAS PASIRLANGU - Ayu Hendrati Rahayu; Rizqy Dimas Monica; Intan Pujilestari (UPPM Politeknik TEDC Bandung, 2020)
Based on preliminary observations, in February 2020 the writer found the problems that were closely related to the outpatient services, especially at the Puskesmas Pasirlangu as follows; (1) Lack of ergonomics in each room there are still spaces that are still narrow resulting in a lack of effectiveness; (2) There are still leaks and humidity in the room, causing mold; (3) improper layout. The purpose of this study was to determine the layout of outpatient services based on the concept of ergonomics in order to support the effectiveness of work in the Pasirlangu Community Health Center. The method used is descriptive with a qualitative analysis approach. Data collection techniques used were observation and interviews. The research instrument used was stationery and interview guidelines. Spatial research results are still not in accordance with the concept of ergonomics because of each room there are shortcomings ranging from lighting, ventilation, room temperature, room humidity and layout that are not yet neat and the effectiveness of work there is not yet fully effective work effectiveness.